Isolation and characterization of phytase enzyme from Escherichia coli - KRISHPA SHAH; PIYUSH DESAI (International Journal of Pharma and Bio Sciences, 2017)
Phytic acid was discovered in 1903, and is found to be nearly ubiquitous component in cereals and grains. It is found to be 80% or more in plants, especially in legumes. Monogastric animals feeding on plants or grains are unable to utilize the phosphate which has been bound to phytic acid. Thus, studies have been centered around a number of phytate degrading enzyme, one of them is phytase enzyme. Phytase is also found to be used in the area of nutrition, environment and biotechnology. It has a capability to hydrolyzed phytate to myoinositol and inorganic phosphate. It releases phosphorus, making it available for absorption and utilization by monogastric animals (hens, chickens, pigs, swines, etc.) and thereby reducing bound phosphorus excretion which is in unusable form creates pollution in environment. Dietary inclusion of phytase in monogastric animals has shown that it can decrease total phosphorus level in the manure. It was found that micro organisms have ability to produce phytase enzyme and hence can be utilized by monogastric animals. Thus bacteria were isolated from the different samples of soil available in valsad and nearby area on general media. Afterwords, isolated bacteria that were able to produce the enzyme phytase were isolated on PSM (phytase screening medium). Enzymes were also tested for its activity which was studied by colorimetric method. The isolated enzyme is found to be extracellular in nature and shows the conversion of phytate to inorganic phosphorus and a positive step towards the problem of Eutrophication.